2016
DOI: 10.1590/1678-457x.12516
|View full text |Cite
|
Sign up to set email alerts
|

Physical-chemical and antimicrobial properties of Egg White Protein Powder films incorporated with orange essential oil on Kashar Cheese

Abstract: In this study, the effects of edible film (EWPP CVV ) produced by the addition (2% v/v) orange essential oil (EO CVV ) to sorbitol (3% w/v) egg white protein powder (EWPP) based film on the physico-chemical and antibacterial properties, appearance (color, structure, brightness) and odor of kashar cheese were studied .Cheese samples were separately coated with these films and stored at +4°C for 30 days. Analyses were performed on the 1st, 7th, 15th and the 30th days of storage. During storage, the inner and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…Whey protein isolate and egg white protein based films incorporated with a variety of essential oils including oregano, clove, ginger, lavender, and orange were found successful as antibacterial biofilms in artificially contaminated kashar cheeses with Listeria monocytogenes, Escherichia coli , and S aureus . This study covers inhibition of molds, which is a more common issue in kashar cheeses . Both fungi population in the plain cheeses with no treatment (T1), UV‐treated samples (T2), and the cheeses packaged with natamycin‐free zein and alginate films (T5) increased to the number, which cannot be enumerated on petri dishes at the end of 30 days of storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whey protein isolate and egg white protein based films incorporated with a variety of essential oils including oregano, clove, ginger, lavender, and orange were found successful as antibacterial biofilms in artificially contaminated kashar cheeses with Listeria monocytogenes, Escherichia coli , and S aureus . This study covers inhibition of molds, which is a more common issue in kashar cheeses . Both fungi population in the plain cheeses with no treatment (T1), UV‐treated samples (T2), and the cheeses packaged with natamycin‐free zein and alginate films (T5) increased to the number, which cannot be enumerated on petri dishes at the end of 30 days of storage.…”
Section: Resultsmentioning
confidence: 99%
“…This study covers inhibition of molds, which is a more common issue in kashar cheeses. [29][30][31][32] Both fungi population in the plain cheeses with no treatment (T1), UV-treated samples (T2), and the cheeses packaged with natamycin-free zein and alginate films (T5) increased to the number, which cannot be enumerated on petri dishes at the end of 30 days of storage. Since there was no subsequent inoculation in these samples, this late domination of natural fungi could be explained with their long adaptation phase because of the presence of other competitor microflora.…”
Section: Application Of the Films To Kashar Cheesementioning
confidence: 99%
“…[ 279 ] Examples of using egg white proteins for food preservation include reduced moisture loss from egg albumen‐coated raisins when stored with bran flakes, [ 280 ] less dehydration and enhanced shell strength of eggs coated with egg albumen solution, [ 281 ] and increased shelf‐life of cheese coated with essential oil‐incorporated egg white protein powder films. [ 282 ] Egg white‐coated potato slices showed a 12% reduction in oil uptake, 30–50% decrease in peroxide amount, and better water retention after being deep‐fried, compared to uncoated potato slices. [ 283 ] Egg white proteins in their original forms are also allergenic but their allergenicity can be diminished to a harmless level through extensive heating.…”
Section: Edible Coatings For Food Preservationmentioning
confidence: 99%
“…It had been demonstrated that the properties of egg white protein (EW) based films were similar to those of protein based films (Haq, Hasnain, & Azam, 2014). The EW films were brighter and more transparent than soybean protein, gluten and corn based films (Kavas & Kavas, 2016). EW was also rich in disulfide bond and sulfhydryl group, which had excellent film‐forming properties (Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%